Social responsibility initiative: examining the influence of a collaborative service learning project on student learning. Issue 3 (2nd September 2019) - Hwang, Chanmi; Liu, Hang; Salusso, Carol J.
ABSTRACT: The purpose of this research was to examine how a collaborative service learning project (CSL) influenced student learning experience. Specific research objectives were to (a) examine student learning experience related to a CSL project, (b) examine how service learning, civic responsibility, and enjoyment influence student academic development, and (c) propose a social responsibility initiative framework for a multi-class CSL project. The findings show that project-based service-learning experience results in both cognitive and affective dimensions of learning where affective dimensions of perceived enjoyment, service learning, and civic responsibility positively influenced academic development. This demonstration project may provide guidance for educators in identifying service learning projects that could expand student learning and also enhance the capacity to foster social responsibility initiatives in their apparel and textile curriculum.